Role of ILC2s in Solid Tumors: Facilitate or Inhibit? - Wu, Lige; Zhao, Weiqing; Tang, Shuxian; Chen, Rui; Ji, Mei; Yang, Xin (Frontiers in Immunology, 2022)
Group 2 innate lymphoid cells (ILC2s) are important mediators of type 2 immunity and play an important role in allergic diseases, helminth infections, and tissue fibrosis. However, the role of ILC2s in tumor immunity requires further elucidation. Studies over the past decade have reported that ILC2s play a promoting or suppressing role in different tumors. Here we reviewed the role of ILC2s in solid tumors demonstrating that ILC2s act as a crucial regulator in tumor immunity. We proposed that ILC2s could be an important predictor for tumor prognosis and a new therapeutic target after immunotherapy resistance. In conclusion, our study shed new light on modifying and targeting ILC2s for anti-tumor immunotherapy.